The Influence of Using Crossword Puzzle Towards Students Vocabulary Mastery - qurani, nada shofia (JURNAL PENDIDIKAN, 2023)
This research is a quantitative study with the aim of determining the influence of using crossword puzzle towards students' vocabulary mastery in grade VII at Mts Darissulaimaniyyah. The technique to collect the data used pre-test and post-test. The results of the pre-test and post-test control class 1) the average pre-test score was 45.053 with the highest score of 60 and the lowest score of 26.6 and the post-test average was 48.543 with the highest score 66.6 and the lowest score 33.3. 2) the results of the pre-test and post-test in the experimental class. The average pre-test score was 45.204 with the highest score 60 and the lowest score 20 and the average score of the post-test student was 85.995 with the highest score of 100 and the lowest score of 73.3. 3) based on the results of the different test using the Mann Whitney test, the results were 0.00 < 0.05, this indicates that Ha is accepted and H0 is rejected. Based on the data analysis, the writer concludes that there was influence of using crossword puzzle towards students’ vocabulary mastery in grade VII at Mts Darissulaimaniyyah